2009
DOI: 10.1520/jai101270
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Wall-Window Interface Details to Manage Rainwater—Selected Results from Window Installation to a Wall Sheathed in Extruded Polystyrene

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…It is therefore of importance to choose dosage rates based on expected infiltration rates that can be obtained by laboratory studies on watertightness testing or from field studies for which water entry in wall assemblies has been monitored. In this study flow rates of 0.057 6 0.001 l/min for multiple entry points or a total flow rate of 0.693 6 0.006 l/ min (= 2.888 6 0.025 l/min.m over a length of 240 mm or 1.925 6 0.017 l/min.m 2 for a specimen area of 0.36 m 2 ) and 0.090 6 0.001 l/min for a single entry point as maximum values based on infiltration rates obtained in laboratory studies on different wall assemblies (Lacasse et al, 2003(Lacasse et al, , 2009(Lacasse et al, , 2019Olsson, 2016aOlsson, , 2016b.…”
Section: Test Methodsmentioning
confidence: 99%
“…It is therefore of importance to choose dosage rates based on expected infiltration rates that can be obtained by laboratory studies on watertightness testing or from field studies for which water entry in wall assemblies has been monitored. In this study flow rates of 0.057 6 0.001 l/min for multiple entry points or a total flow rate of 0.693 6 0.006 l/ min (= 2.888 6 0.025 l/min.m over a length of 240 mm or 1.925 6 0.017 l/min.m 2 for a specimen area of 0.36 m 2 ) and 0.090 6 0.001 l/min for a single entry point as maximum values based on infiltration rates obtained in laboratory studies on different wall assemblies (Lacasse et al, 2003(Lacasse et al, , 2009(Lacasse et al, , 2019Olsson, 2016aOlsson, , 2016b.…”
Section: Test Methodsmentioning
confidence: 99%
“…Lacasse et al [12] evaluated the performance of face-sealed and drained sealing methods for vinyl windows installed in wood-frame walls sheathed with extruded polystyrene foam insulation board. It was concluded that when a rubber gasket was installed at the exterior joint between the window frame and the cladding in a facesealed manner, a significantly smaller amount of water was collected behind the cladding compared to the drained specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The test program described in this manuscript followed that used in previous studies [10,11,12]; the ability of different wall-window installation details to manage rainwater was determined on the basis of watertightness tests and the response of the respective interface details to simulated conditions of wind-driven rain.…”
Section: Experimental Approach To Evaluating Water Management Of Windmentioning
confidence: 99%
“…The Dynamic Wind and Wall Test Facility (DWTF), used to subject similar specimens to simulated winddriven rain conditions in previous studies [10,11,12,16] was used in this investigation. The facility is capable of subjecting full-scale test specimens (nominal size 2.44 by 2.44-m) to static levels of air pressure differential or to air pressure differentials that fluctuate dynamically; the dynamic pressure fluctuation capabilities of the facility were not however used in this investigation.…”
Section: Description Of Test Apparatusmentioning
confidence: 99%
See 1 more Smart Citation